1989
DOI: 10.1007/bf01912936
|View full text |Cite
|
Sign up to set email alerts
|

A thermal analysis study of the oxidation of brown coal chars

Abstract: The combustion of brown coal chars, obtained at different pyrolysis temperatures, have been investigated using TG, DTG and DTA thermal analysis methods. The burning profiles and the kinetic parameters derived from TG and DTA data show that all the chars are less reactive than the parent coal. The higher temperature chars have lower overall reactivity. From the corresponding infrared spectra, the chars obtained at 800"~ and I000 ~ appear to have graphitic structures.Victorian brown coal is a low rank, non-cokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Studies on the thermal analysis of Victorian brown coal to determine pyrolysis and combustion kinetics can be found in the open literature [14][15][16][17][18][19]. However, very few studies reported provided information on the gasification kinetics of Victorian brown coals; those available were summarised by Bhattacharya et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the thermal analysis of Victorian brown coal to determine pyrolysis and combustion kinetics can be found in the open literature [14][15][16][17][18][19]. However, very few studies reported provided information on the gasification kinetics of Victorian brown coals; those available were summarised by Bhattacharya et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…В целом характер полученного ИК-спектра идентичен таковым бурых углей (суббитуминозных лигнитов по европейской классификации) [Файзулина, 1967;Ma et al, 1989;Saikia et al, 2007].…”
Section: рис 12 надмолекулярная структура угля (а) и кривая програмunclassified
“…Ma et al [15] have applied simultaneous TG-DTG/DTA techniques to derive kinetic parameters for the oxidation of a brown coal sample and a series of corresponding chars. The DTG burning profile of Loy Yang coal and a series of corresponding chars obtained at various temperatures are shown in Fig.…”
Section: [mentioning
confidence: 99%